(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: Non-alcoholic fatty liver disease (NAFLD) is common in T2DM, because of insulin resistance and obesity. In obese diabetic patients, NAFLD can be prevented and treated by reducing weight by diet and making regular exercises. The objective of the study was to evaluate the frequency of NAFLD in patients having Type 2 DM. Materials and Methods: Study Design: Descriptive cross sectional study Place and Duration of the Study: This study was conducted at the department of medicine, Saidu group of teaching Hospital Swat from Jan 2018 to Jul 2018. Sample size: 145 patients Blood samples of 145 patients were taken with consecutive (non-probability) technique for lipid and glycemic profiles and liver enzymes. Diagnosis of NAFLD was done with ultrasound using Sonoline 450 (B-mode, Probe 3.5Mhz). Results: Our results showed the presence of NAFLD in 51% (n=74) in a total of 145 patients 49(71%) male and 51(74%) female patients having raised BMI (p < 0.001)and hypertension (p < 0.001). Metabolic syndrome was found to be frequent in patients with NAFLD. Serum triglyceride and serum cholesterol were significantly raised in NAFLD patients. Conclusion: Nonalcoholic fatty liver disease (NAFLD) is more commonly seen in Type-2 diabetic patients with elevated BMI as well as serum triglycerides and serum cholesterol levels. Routine screening of diabetic patients for NAFLD is not currently recommended.